Analisis Kesiapsiagaan Di Fasilitas Pelayanan Kesehatan Terhadap Tanggap Darurat Bencana Kebakaran - Alif Araafi; Ella Asri Fauziah; Sarda Mauliyand; Abdurrozzaq Hasibuan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
Preparedness is a series of actions taken to anticipate disasters through planning and implementing reasonable and practical actions known as preparedness. One of the Occupational Safety and Health (K3) requirements that must be implemented by health service facilities is preparedness for fire disasters. This literature evaluation aims to assess the level of preparedness of health service facilities in handling crises involving fire. The findings of the literature review show the importance of preparing human resources for fire management education and training, providing fire extinguishers and other fire management related infrastructure, and forming a team of K3 coordinators and fire management experts.